Assessing Zika Virus Transmission Within Households During an Outbreak in Martinique, 2015–2016. Issue 7 (17th April 2019) - Cousien, Anthony; Abel, Sylvie; Monthieux, Alice; Andronico, Alessio; Calmont, Isabelle; Cervantes, Minerva; Césaire, Raymond; Gallian, Pierre; de Lamballerie, Xavier; Laouénan, Cédric; Najioullah, Fatiha; Pierre-François, Sandrine; et al.
Abstract: Since 2015, Zika virus (ZIKV) has caused large epidemics in the Americas. Households are natural targets for control interventions, but quantification of the contribution of household transmission to overall spread is needed to guide policy. We developed a modeling framework to evaluate this contribution and key epidemic features of the ZIKV epidemic in Martinique in 2015–2016 from the joint analysis of a household transmission study ( n = 68 households), a study among symptomatic pregnant women ( n = 281), and seroprevalence surveys of blood donors ( n = 457). We estimated that the probability of mosquito-mediated within-household transmission (from an infected member to a susceptible one) was 21% (95% credible interval (CrI): 5, 51), and the overall probability of infection from outside the household (i.e., in the community) was 39% (95% CrI: 27, 50). Overall, 50% (95% CrI: 43, 58) of the population was infected, with 22% (95% CrI: 5, 46) of infections acquired in households and 40% (95% CrI: 23, 56) being asymptomatic. The probability of presenting with Zika-like symptoms due to another cause was 16% (95% CrI: 10, 23). This study characterized the contribution of household transmission in ZIKV epidemics, demonstrating the benefits of integrating multiple data sets to gain more insight into epidemic dynamics.